2022
DOI: 10.3389/fpsyg.2022.790424
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Form-Focused Instruction on the L2 Chinese Oral Production of Korean Native Speakers

Abstract: Form-focused instruction (FFI) can help second language (L2) learners notice the forms of language, which is conducive to the acquisition of linguistic forms. Two types of FFIs had been proposed, including focus-on-formS (FonFs) and focus-on-form (FonF). Previously, studies on FFI in L2 classroom teaching have focused mainly on the influence of two types of FFIs on the L2 acquisition of grammar and vocabulary. The influence of FonFs and FonF on L2 oral production, however, has been addressed less often. The ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…To our knowledge, the current paper is the first systematic study of CSFL textbooks to examine their cultural representation and reconstruction. Regarding the first research question in the study, our results are mainly supportive of the general consensus, as well as offering some new findings: (1) In contrast to a common perception that China's foreign language education is not communicative enough and is traditionally form-focused (Chen & Li, 2022), we found that current CSFL textbooks generally include rich Hispanic cultural content. In particular, small "c" cultural products were emphasized over big "C" aspects.…”
Section: Discussionsupporting
confidence: 79%
“…To our knowledge, the current paper is the first systematic study of CSFL textbooks to examine their cultural representation and reconstruction. Regarding the first research question in the study, our results are mainly supportive of the general consensus, as well as offering some new findings: (1) In contrast to a common perception that China's foreign language education is not communicative enough and is traditionally form-focused (Chen & Li, 2022), we found that current CSFL textbooks generally include rich Hispanic cultural content. In particular, small "c" cultural products were emphasized over big "C" aspects.…”
Section: Discussionsupporting
confidence: 79%
“…In summary, no matter what kind of instruction conditions were used for the learners, the learning effects for lexical forms were maintained better than the syntactic forms, and the learning effects for syntactic complexity were the worst. The explanation for this is that syntactic abilities, such as sentence structure organization, cohesive construction, and semantic integration were more difficult to acquire because of their weak explicitness (Ahmadian and Tavakoli, 2011;Chen and Li, 2016;Kang et al, 2019), and more cognitive efforts were needed to increase the number of AS-unit clauses. Therefore, it is necessary to explore the relationship between learners' attention to syntactic complexity and oral production.…”
Section: The Interaction Between Instruction Methods and Testing Timementioning
confidence: 99%
“…We used analysis of speech units (AS-units) to calculate complexity and accuracy of oral production (Foster et al, 2000, p. 365). Division into AS-units was achieved based on the characteristics of Chinese syntactic structure, referring to the three principles constructed by Chen and Li (2016). According to the first principle, a single sentence with strong independence is regarded as one AS-unit.…”
Section: Measurement Of Dependent Variablesmentioning
confidence: 99%
“…Thus, some researchers now recognize the necessity of explicit FonFs for advanced language learners and claim that grammar instruction is essential if learners are to achieve their educational and professional goals (Celce-Murcia, 1991;Schmidt, 1994;Shaw & Liu, 1998). Chen and Li (2022) investigated the effects of FonFs and FonF on L2 Chinese oral production. The results of their study showed that, for high-proficiency learners, it is not sufficient to pay attention only to meaning (FonF); the linguistic forms should also be given continuous attention (FonFs).…”
Section: Focus On Form Vs Focus On Formsmentioning
confidence: 99%